The effect of disability insurance receipt on labor supply: A dynamic analysis - Eric French; Jae Song (Federal Reserve Bank of Chicago, 2012)
This paper estimates the effect of Disability Insurance receipt on labor supply, accounting for the dynamic nature of the application process. Exploiting the effectively random assignment of judges to disability insurance cases, we use instrumental variables to address the fact that those allowed benefits are a selected sample. We find that benefit receipt reduces labor force participation by 26 percentage points three years after a disability determination decision when not considering the dynamic nature of the applications process. OLS estimates are similar to instrumental variables estimates. We also find that over 60% of those denied benefits by an Administrative Law Judge are subsequently allowed benefits within 10 years, showing that most applicants apply, re-apply, and appeal until they get benefits. Next, we estimate a dynamic programming model of optimal labor supply and appeals choices. Consistent with the law, we assume that people cannot work and appeal at the same time. We match labor supply, appeals, and subsequent allowance decisions predicted by the model to the decisions observed in the data. We use the model to predict labor supply responses to benefit denial when there is no option to appeal. We find that if there was no appeals option, those denied benefits are 35 percentage points more likely to work. However, there is considerable heterogeneity in responses. Most individuals 40s would return to work if denied benefits, for example. Our results suggest that many of those denied benefits not because they are unable to work, but because they remain out of the labor force in order to appeal their benefit denial.
Keywords: 330